2007
DOI: 10.1002/pssc.200675851
|View full text |Cite
|
Sign up to set email alerts
|

Positron lifetime studies on the free volume changes during deformation of rubber‐carbon black composites

Abstract: The free volume behavior as a function of strain during deformation of natural rubber-carbon black composites studied by positron annihilation lifetime spectroscopy (PALS) is reported. The lifetime and intensity of the ortho-positronium (o-Ps) pick-off annihilation, which correlate with the average size and the number of holes respectively, were measured as a function of strain. The results show how PALS can detect the changes that occur in polymer composites samples and help explain the effect of carbon black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Positron annihilation lifetime spectroscopy is a very useful technique for structural characterization in polymers, especially at the nanoscale, for the aforementioned reasons and, therefore, has been extensively used to investigate CB-filled rubber composites. [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] Nonetheless, those studies remained mostly inconclusive due to inconsistencies in the results of different groups and the difficulty in effectively relating the o-Ps data to the viscoelastic properties of the rubber and the networkchain density. For instance, some of the earlier works detected a variation of the o-Ps lifetime as a function of CB concentration, whereas other studies simply reported that the o-Ps lifetime depends only on the type of rubber composite but is independent of the CB loading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positron annihilation lifetime spectroscopy is a very useful technique for structural characterization in polymers, especially at the nanoscale, for the aforementioned reasons and, therefore, has been extensively used to investigate CB-filled rubber composites. [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] Nonetheless, those studies remained mostly inconclusive due to inconsistencies in the results of different groups and the difficulty in effectively relating the o-Ps data to the viscoelastic properties of the rubber and the networkchain density. For instance, some of the earlier works detected a variation of the o-Ps lifetime as a function of CB concentration, whereas other studies simply reported that the o-Ps lifetime depends only on the type of rubber composite but is independent of the CB loading.…”
Section: Introductionmentioning
confidence: 99%
“…Positron annihilation lifetime spectroscopy is a very useful technique for structural characterization in polymers, especially at the nanoscale, for the aforementioned reasons and, therefore, has been extensively used to investigate CB‐filled rubber composites 48–64 . Nonetheless, those studies remained mostly inconclusive due to inconsistencies in the results of different groups and the difficulty in effectively relating the o ‐Ps data to the viscoelastic properties of the rubber and the network‐chain density.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have given considerable attention to the change of free‐volume in CB filled rubber composites by using PALS during the curing of composites or during deformation while, others prepared a blend of different types of rubber. On our knowledge, such study on an attractive and interesting class (type) of rubber, PDMS, has not been undertaken deeply.…”
Section: Introductionmentioning
confidence: 99%